Implementation of Tolerance Character Education: A Comparative Study on Indonesia and Finland Elementary Schools - Khotimah, Rifaa Husnul; Hidayat, Muhamad Taufik (Universitas Muhammadiyah Surakarta, 2023)
Purpose: This study aims to compare the implementation of tolerance in elementary schools in Indonesia and Finland. Methods: The method used was qualitative descriptive with a literature study design. The type of study used was a comparative literature review. Data obtained were secondary data, including articles in online scientific journals, website articles, and books related to the implementation of character education of tolerance in Indonesia or Finland elementary schools. Results: Elementary schools in Indonesia or Finland have their own method of implementing character education, especially tolerance. Both countries have varied methods to implement tolerance values. This implementation is not only carried out in the class but also outside the class. However, from various methods and strategies used by schools in those countries, the two countries actually have several differences. In Indonesia, the implementation of tolerance values is still often carried out in the school environment by involving schoolmates. However, in Finland, tolerance can be implemented not only with friends from the same school but also with friends from different schools. Moreover, tolerance values in Indonesia are still implemented in existing lessons, while Finland has its own subject discussing life values, such as tolerance. Application/Originality/Value: This study explained methods for implementing tolerance character in Indonesia and Finland elementary schools based on three elements: providing freedom and not forcing others, respecting other beliefs, and understanding each other on existing differences.